Vivências além do olhar: práticas inclusivas no ensino de matemática para alunos com deficiência visual - Guimarães, Gabriela Freire (Universidade Federal de São Carlos, 2025)
This final project focuses primarily on the experience of inclusive practices in teaching mathematics to visually impaired students, highlighting the importance of an accessible, sensitive, and concrete approach to knowledge construction. The research is enriched by the author's own experiences, as a classroom assistant at a private school in Sorocaba, São Paulo, where she has been teaching a visually impaired student for almost four years. Through these experiences, pedagogical adaptations developed in both mathematics and interdisciplinary approaches are presented. The study also promotes reflections on the barriers faced by blind students in the schooling process, highlighting the importance of teacher training, the reorganization of physical spaces, and the adequacy of pedagogical resources. The results indicate that inclusion is viable, even in the face of structural limitations, as long as there is sensitivity, creativity, and ethical commitment on the part of the school staff. It is clear that adaptation does not mean devaluing the content, but rather transforming teaching methods, guaranteeing the right to learn. Furthermore, the presence of tactile materials is essential not only for students with visual impairments, but for all students, respecting the different learning styles.
Experiences beyond the gaze: inclusive practices in teaching mathematics to students with visual impairments
Keywords: Deficiência Visual; Inclusão; Braille; Educação; Matemática; Visual Impairments; Inclusion; Braille; Education; Mathematics; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM